Research trends of music in children with autism: a bibliometric analysis - Tao, Ye; Yu, Chun (Frontiers in Psychiatry, 2025)
IntroductionThe impact of music on children with autism—a condition marked by deficits in social interaction, communication, and behavior—has become a significant area of research. This study investigates current trends, key contributors, and emerging interests regarding music’s effects on this population.MethodsA comprehensive review of publications from 1953 to 2024 on the influence of music on children with autism was conducted using the Web of Science Core Collection. Bibliometric and visual analyses were performed with VOSviewer, CiteSpace, and R version 4.3.3.ResultsA total of 411 research papers were identified, with significant publication growth noted post-2009. The leading countries in this research include the United States, the United Kingdom, Canada, China, and Australia. McGill University ranked as the most prolific institution (23 publications), followed by the University of Montreal (17) and Vanderbilt University (12). The Journal of Autism and Developmental Disorders is the most influential journal, with an h-index of 19 and 1,706 citations. Professor Christian Gold emerged as the top author, with 12 papers totaling 599 citations. Key keywords included “children,” “autism,” and “therapy,” with a noted increase in terms like “social skills,” “communication,” and “engagement” since 2020.ConclusionThis study highlights music’s potential to enhance social and communication skills in children with autism. Future research should explore the long-term effects of music therapy on language, cognition, and behavioral outcomes, as well as its role in improving engagement in educational and therapeutic settings.